Social Exclusion and Learning Engagement among University Students: The Role of Depression and Self-Efficacy - Xiao, Xidan; Li, Kaiyuan (South Sulawesi Education Development, 2025)
Studies have shown that social exclusion has a negative relationship with learning engagement. However, less is known about the underlying processes that may mediate this relationship. Thus, the current investigation aimed to examine the influence of social exclusion on college students' motivation to learn and the mediational roles of depression and self-efficacy in this association. A cross-sectional research design was employed, and a total of 600 Chinese university students participated in the study. The survey materials included the Social Exclusion Questionnaire, Learning Engagement Inventory, Depression Scale, and Self-Efficacy Inventory of the Centre for Fluency Studies. The results revealed that social exclusion significantly and adversely predicted learning engagement among Chinese university students, and both depression and self-efficacy exerted significant mediating effects in the relationship between social exclusion and learning engagement. These findings illuminate the relationship between social exclusion and university students' motivation to learn, as well as the underlying mechanisms that offer not only a theoretical basis for higher education pedagogy but also potential interventions that foster self-efficacy and enhance learning engagement.